Astrocytes in the adult dentate gyrus—balance between adult and developmental tasks - Chalmers, Nicholas; Masouti, Evangelia; Beckervordersandforth, Ruth (Molecular Psychiatry, 2024)
Astrocytes, a major glial cell type in the brain, are indispensable for the integration, maintenance and survival of neurons during development and adulthood. Both life phases make specific demands on the molecular and physiological properties of astrocytes, and most research projects traditionally focus on either developmental or adult astrocyte functions. In most brain regions, the generation of brain cells and the establishment of neural circuits ends with postnatal development. However, few neurogenic niches exist in the adult brain in which new neurons and glial cells are produced lifelong, and the integration of new cells into functional circuits represent a very special form of plasticity. Consequently, in the neurogenic niche, the astrocytes must be equipped to execute both mature and developmental tasks in order to integrate newborn neurons into the circuit and yet maintain overall homeostasis without affecting the preexisting neurons. In this review, we focus on astrocytes of the hippocampal dentate gyrus (DG), and discuss specific features of the astrocytic compartment that may allow the execution of both tasks. Firstly, astrocytes of the adult DG are molecularly, morphologically and functionally diverse, and the distinct astrocytes subtypes are characterized by their localization to DG layers. This spatial separation may lead to a functional specification of astrocytes subtypes according to the neuronal structures they are embedded in, hence a division of labor. Secondly, the astrocytic compartment is not static, but steadily increasing in numbers due to lifelong astrogenesis. Interestingly, astrogenesis can adapt to environmental and behavioral stimuli, revealing an unexpected astrocyte dynamic that allows the niche to adopt to changing demands. The diversity and dynamic of astrocytes in the adult DG implicate a vital contribution to hippocampal plasticity and represent an interesting model to uncover mechanisms how astrocytes simultaneously fulfill developmental and adult tasks.
CRIS-Team Scopus Importer:2024-01-12

Dentate gyrus astrocytes exhibit layer-specific molecular, morphological and physiological features - Karpf, Julian; Unichenko, Petr; Chalmers, Nicholas; Beyer, Felix; Wittmann, Marie-Theres; Schneider, Julia; Fidan, Elif; Reis, André; Beckervordersandforth, Jan; Brandner, Sebastian; Liebner, Stefan; Falk, Sven; et al. (Nature Neuroscience, 2022)
Neuronal heterogeneity has been established as a pillar of higher central nervous system function, but glial heterogeneity and its implications for neural circuit function are poorly understood. Here we show that the adult mouse dentate gyrus (DG) of the hippocampus is populated by molecularly distinct astrocyte subtypes that are associated with distinct DG layers. Astrocytes localized to different DG compartments also exhibit subtype-specific morphologies. Physiologically, astrocytes in upper DG layers form large syncytia, while those in lower DG compartments form smaller networks. Astrocyte subtypes differentially express glutamate transporters, which is associated with different amplitudes of glutamate transporter-mediated currents. Key molecular and morphological features of astrocyte diversity in the mice DG are conserved in humans. This adds another layer of complexity to our understanding of brain network composition and function, which will be crucial for further studies on astrocytes in health and disease.
CRIS-Team Scopus Importer:2022-12-09

Distinct forebrain regions define a dichotomous astrocytic profile in multiple system atrophy - Schneider, Yanni; Gauer, Carina; Andert, Marie; Hoffmann, Alana; Riemenschneider, M. J.; Krebs, W.; Chalmers, Nicholas; Lötzsch, C.; Naumann, Ulrike; Xiang, Wei; Rothhammer, Veit; Beckervordersandforth, Ruth; et al. (Acta Neuropathologica Communications, 2024)
The growing recognition of a dichotomous role of astrocytes in neurodegenerative processes has heightened the need for unraveling distinct astrocytic subtypes in neurological disorders. In multiple system atrophy (MSA), a rare, rapidly progressing atypical Parkinsonian disease characterized by increased astrocyte reactivity. However the specific contribution of astrocyte subtypes to neuropathology remains elusive. Hence, we first set out to profile glial fibrillary acidic protein levels in astrocytes across the human post mortem motor cortex, putamen, and substantia nigra of MSA patients and observed an overall profound astrocytic response. Matching the post mortem human findings, a similar astrocytic phenotype was present in a transgenic MSA mouse model. Notably, MSA mice exhibited a decreased expression of the glutamate transporter 1 and glutamate aspartate transporter in the basal ganglia, but not the motor cortex. We developed an optimized astrocyte isolation protocol based on magnetic-activated cell sorting via ATPase Na+/K+ transporting subunit beta 2 and profiled the transcriptomic landscape of striatal and cortical astrocytes in transgenic MSA mice. The gene expression profile of astrocytes in the motor cortex displayed an anti-inflammatory signature with increased oligodendroglial and pro-myelinogenic expression pattern. In contrast, striatal astrocytes were defined by elevated pro-inflammatory transcripts accompanied by dysregulated genes involved in homeostatic functions for lipid and calcium metabolism. These findings provide new insights into a region-dependent, dichotomous astrocytic response—potentially beneficial in the cortex and harmful in the striatum—in MSA suggesting a differential role of astrocytes in MSA-related neurodegenerative processes.
CRIS-Team Scopus Importer:2024-01-12